KASUS BO XILAI SEBAGAI IMPLIKASI DARI PROSES PERALIHAN KEPEMIMPINAN PARTAI KOMUNIS CINA - , AYUNDA RAHMANI KHOIRUNNISSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research analyses Bo Xilai case, one of the most complicated political scandals in the era of modern Chinese. Using bureaucratic politics model, theory of tendency conflict, and political corruption concept, this research has found that to some extent, Bo Xilai case was relevant to Chinese Communist Partyâs leadership transition. Bo Xilaiâs corruption scandal has become a major political phenomenon because it tested the legitimacy and solidity of the ruling party of China. Bo Xilaiâs expel from power has also indicated how the competition between Chongqing model and Guangdong model impacted factionalism in China. However, the most important aspect is that Bo Xilai case has revealed the existence of power struggle among Chinese elites for the countryâs most prominent leadership transition: 18th Party National Congress in 2012.